The Effect of Viral Marketing and Brand Image on Purchase Decisions Through e-Trust: (Study on Kahf Skincare Customers) - Fatah, Muh. Al; Arsyad, Miftahul Jannah (PT. Maju Malaqbi Makkarana, 2022)
Viral Marketing is a trend that is able to attract the attention of consumers through social media. This study aims to determine the effect of viral marketing and brand image on purchase decisions through e-trust. This research is a quantitative study using the SPSS 22 program. The population in this study is Kahf's Instagram followers. The sample in this research is 200 respondents. In addition, to test the feasibility of the instrument used validity and reliability tests, classical assumption tests, and hypothesis testing. Path analysis analysis technique. The results of this study indicate that (1) viral marketing has a positive and significant effect on e-trust, (2) brand image has a positive and significant effect on e-trust (3) viral marketing has a positive and significant effect on purchase decisions, (4) brand image has a positive and significant effect on purchase decision, (5) e-trust has a positive and significant effect on purchase decision. Based on the research results, suggestions for business actors provide more attractive advertisements for consumers, make product designs more attractive, and set products according to needs.